Critical thinking : (McGraw-Hill, 2008)
This clear, learner-friendly text helps today's students bridge the gap between everyday culture and critical thinking. The text covers all the basics of critical thinking, beginning where students are, not where we think they should be. Its comprehensiveness allows instructors to tailor the material to their individual teaching styles, resulting in an exceptionally versatile text.